Bio-Hybrid Membrane Process for Food-based Wastewater Valorisation: a pathway to an efficient integrated membrane process design - Gebreyohannes, Abaynesh Yihdego; Giorno, Lidietta; Curcio, Efrem; Aimar, Pierre; Vankelecom, Ivo F.J.; Molinari, Raffaele (My University, 2014)
The food industry is by far the largest potable water consuming industry that releases about 500 million m3 of wastewater per annum with very high organic loading. Simple treatment of this stream using conventional technologies often fails due to cost factors overriding their pollution abating capacity. Hence, recently the focus has been largely centered on valorization through combinatorial recovery of valuable components and reclaiming good quality water using integrated membrane process. Membrane processes practically cover all existing and needed unit operations that are used in wastewater treatment facilities. They often come with advantages like simplicity, modularity, process or product novelty, improved competitiveness, and environmental friendliness. Thus, the main focus of this PhD thesis is development of integrated membrane process comprising microfiltration (MF), forward osmosis (FO), ultrafiltration (UF) and nanofiltration (NF) for valorization of food based wastewater within the logic of zero liquid discharge. As a case study, vegetation wastewater coming from olive oil production was taken. Challenges associated with the treatment of vegetation wastewater are: absence of unique hydraulic or organic loadings, presence of biophenolic compounds, sever membrane fouling and periodic release of large volume of wastewater. Especially presence of biophenolic compounds makes the wastewater detrimental to the environment. However, recovering these phytotoxic compounds can also add economic benefit to the simple treatment since they have interesting bioactivities that can be exploited in the food, pharmaceutical and cosmetic industries. The first part of the experimental work gives special emphasis on the development of biohybrid membranes used to control membrane fouling during MF. Regardless of 99% TSS removal with rough filtration, continuous MF of vegetation wastewater using 0.4 μm polyethelene membrane over 24 h resulted in continuous flux decline. This is due to sever membrane fouling mainly caused by macromolecules like pectins. To overcome the problem of membrane fouling, biocatalytic membrane reactors with covalently immobilized pectinase were used to develop self-cleaning MF membrane. The biocatalytic membrane with pectinase on its surface gave a 50% higher flux compared to its counterpart inert membrane. This better performance was attributed to simultaneous in-situ degradation of foulants and removal of hydrolysis products from reaction site that overcome enzyme product inhibition. Although the biocatalytic membrane gave a better performance, its fate is disposal once the covalently immobilized enzyme gets deactivated or oversaturated with foulants. To surmount this problem a new class of superparamagnetic biochemical membrane reactor was developed, verified and optimized. This development is novel for its use of superparamagnetic nanoparticles both as support for the immobilized enzyme and as agent to render the membrane magnetized. This reversible immobilization method was designed to facilitate the removal of enzyme during membrane cleaning using an external magnet. Hence PVDF based organic-inorganic (O/I) hybrid membrane was prepared using superparamagnetic nanoparticles (NPSP) as inorganic filler. In parallel, superparamagnetic biocatalytic nanocomposites were prepared by covalently immobilizing pectinase on to the surface of NPSP dispersed in aqueous media. The synergetic magnetic responsiveness of both the O/I hybrid membrane and the biocatalytic particle to an external magnetic field was later on used to physically immobilize the biocatalytic particles on the membrane. This magnetically controlled dynamic layer of biocatalytic particles prevented direct membrane-foulant interaction, allowed in-situ degradation, easy magnetic recovery of the enzyme from the surface of the membrane, use of both membrane and immobilized enzyme over multiple cycles and possibility of fresh enzyme make up. The system gave stable performance over broad range of experimental condition: 0.01-3 mg/mL foulant concentration, 1-9 g per m2 of membrane area bionanocomposites, 5- 45 L/m2.h flux and different filtration temperatures. Under condition of mass transfer rate prevailing reaction rate, the system gave upto 75% reduction in filtration resistance. After optimization of the different operational parameters, it also revealed no visible loss in enzyme activity or overall system performance, when 0.3 mg/mL pectin solution was continuously filtered for over two weeks. In addition, the chemical cleaning stability of the O/I hybrid membrane was studied under accelerated ageing and accelerated fouling conditions. The ageing caused change in the physicochemical characteristics and enhanced fouling propensity of the membrane due to step-by-step degradation of the polymeric coating layer of used NPSP. But 400 ppm NaOCl solution at pH 12 was found compatible; henceforth it was used to clean the membrane. Second major limitation identified during the treatment of vegetation wastewater is presence of large volume of wastewater that comes in short period following the harvest of olive fruit. To alleviate this problem, FO was investigated to concentrate the wastewater. This process is believed to be less energy demanding, suppose that draw solution does need to be regenerated, and with low foul propensity. By operating at 3.7 molal MgCl2 draw solution and 6 cm/s crossflow velocity, single-step FO resulted in an average flux of 5.2 kg/m2.h. and 71% volume concentration factor with almost complete retention of all the pollutants. Moreover, the system gave a stable performance over ten days when operated continuously. After FO, both NF and UF were used to fractionate the recovered biophenols from the concentrate streams of FO. Compared to polymeric UF membrane, ceramic NF gave better flux of 27 kg/m2.h at 200 L/h feed flow rate and 7 bar TMP. Finally, when FO was used as a final polishing step to recover highly concentrated biophenols from permeate of the UF; it gave an average flux of 5 kg/m2.h and VCF of 64%. In conclusion, a great success has been made in tackling the two most important challenges of vegetation wastewater valorisation using the concept of biohybridization and FO. The bioinspired NPSP provides strong evidence that magnetically controlled enzyme immobilization have an immense potential in membrane fouling prevention and paves a potential breakthrough for continuous wastewater filtration. By setting bio-inspired NPSP biocatalytic membrane reactor at the heart, it is possible to successfully use integrated membrane process for continuous valorisation of food based wastewater. In addition to fouling prevention, they open a new horizon for applications in localized biocatalysis to intensify performance in industrial production, processing, environmental remediation or bio-energy generation.
Dottorato di Ricerca in Ingegneria Chimica dei Materiali, Ciclo XXVII, a.a. 2013-2014
Keywords: Ingegneria chimica; Acque reflue